Moderating Competency on the Effect of Owner’s IQ, EQ, and SQ on MSME Performance in Denpasar City - Luh Putri Mas Mirayani; RR. Maria Yulia Dwi Rengganis; Putu Ayu Anggya Agustina (AIBPM Publisher, 2022)
National development of a nation includes economic development and Micro, Small and Medium Enterprises (MSMEs). The performance of MSMEs needs to be investigated because the contribution of the MSME sector to Gross Domestic Product (GDP) has increased from 57.84% to 60.34% in the last 5 years. This study aims to determine the effect of IQ, EQ, and SQ on the performance of Micro, Small and Medium Enterprises moderated by competence. The object of research is the performance of MSMEs in Denpasar City. The sampling technique used in this study is Probably sampling using a simple random technique. There are 100 MSMEs as a sample with a total of 77 statements. Based on the results of research analysis (1) competence weakens the positive influence of IQ and SQ on the performance of MSMEs in Denpasar City; and (2) competence is not able to moderate the effect of EQ on the performance of MSMEs in Denpasar City. Suggestions for further research are to develop research objects and develop research instruments by conducting personal interviews with respondents.Â Keywords: IQ, EQ, SQ, Competence, Performance.